Occurrence, antibiotic resistance and genetic deiversity of arcobacter isolates from cattle and goats - Shah, Sayed Atta Hussain (2012)
Arcobacter is considered as one of the emerging food and water borne zoonotic pathogens. It has been isolated from various species of animals, animal origin food products, vegetables, and water. Most of the studies on detection and characterization of Arcobacter have been carried out in developed countries whereas such data is lacking in developing countries like Malaysia. With this scenario in view, this study was carried out to isolate Arcobacter spp. from cattle, goats, milk, beef and water, to determine its antimicrobial resistance patterns and to evaluate the genetic diversity of the isolates. A total of six dairy cattle farms in Rawang (A), UPM (B), Serdang (C), Kuala Kubu Baru (D), and Sepang (E) in Selangor and in Tampin (F) in Negeri Sembilan were visited for collection of cattle rectal swabs (adults, n=120; young=120), water (n=18) and environmental surfaces (n=30) samples. The occurrence of Arcobacter in adult cattle on farm A, B, C, D, E and F was recorded as 10% (2/20), 5% (1/20), 0% (0/20),0% (0/20), 10% (2/20) and 15% (3/20), respectively whereas for young cattle the occurrences were, 5% (1/20), 0% (0/20), 10% (2/20), 10% (2/20), 0% (0/20) and 5% (1/20), respectively. The overall prevalence of Arcobacter in adult cattle was 6.7% (8/120) and in the young was 5% (6/120) which was non-significant (p=0.584). Arcobacter was not detected in floor samples collected from farm A, however 40% of samples from farm B, C, D and F each, and 20% from farm E were detected positive. Arcobacter was not detected from treated water from all farms except farm F (66.7%). In total, 8 of 30 (26.66%) floor samples and 2 of 18 (11.11%) treated water samples examined were positive for Arcobacter. Overall, Arcobacter butzleri was the most frequently isolated species 9/24 (37.5%) followed by Arcobacter skirrowii 1/24 (4.1%). A total of 140 samples including goat rectal swabs (n=100), water (n=15) and floor swabs (n=25) were collected from five goat farms in Rawang, Sepang, Kuala Kubu Baru, Cyberjaya in Selangor and Nilai in Negeri Sembilan and found negative for Arcobacter spp. A total of 148 beef samples, local (n=85) and imported (n=63) and 180 milk samples,cattle (n=86) and goats (n= 94) were collected. Overall, 26.35% (39/148) beef samples were found positive for Arcobacter. Imported beef was more contaminated (39.68%) than local (16.47%) beef. Arcobacter butzleri was the most frequent species isolated from imported (52%) and local (35.71%) beef. Arcobacter was also detected from cattle milk (5.43%) with A. butzleri as the dominant species (60%) followed by A. cryaerophilus (40%). None of the goat milk samples was found positive for Arcobacter. Using minimum Inhibitory Concentration Evaluator (M.I.C.E) and disc diffusion methods, the A. butzleri isolates from cattle (n=5), beef (n=15), milk (n=3), water (1) and floor (n=2) were tested against six antibiotics namely ampicillin, ciprofloxacin,erythromycin, tetracycline, cefotaxime and gentamicin. None of the A. butzleri isolates was found resistant to all six antibiotics tested. A wide range of A. butzleri isolates were found resistant to antibiotics using both techniques: 74.07-81.48% for ampicillin, 22.22-25.92% for ciprofloxacin, 37.03-70.37% for erythromycin, 7.4-11.11% for tetracycline, 55.55-70.37% for cefotaxime and 18.51-22.22% for gentamicin,Using minimum Inhibitory Concentration Evaluator (M.I.C.E) and disc diffusion methods, the A. butzleri isolates from cattle (n=5), beef (n=15), milk (n=3), water (1) and floor (n=2) were tested against six antibiotics namely ampicillin, ciprofloxacin,erythromycin, tetracycline, cefotaxime and gentamicin. None of the A. butzleri isolates was found resistant to all six antibiotics tested. A wide range of A. butzleri isolates were found resistant to antibiotics using both techniques: 74.07-81.48% for ampicillin, 22.22-25.92% for ciprofloxacin, 37.03-70.37% for erythromycin, 7.4-11.11% for tetracycline, 55.55-70.37% for cefotaxime and 18.51-22.22% for gentamicin, respectively. Of the resistant isolates, 3.70% and 11.11% isolates were found MDR using M.I.C.E and disc diffusion methods, respectively. The lowest minimum inhibitory concentrations (MICs), MIC50/MIC90 values were obtained for tetracycline (0.03/4 μg/mL) however highest for ampicillin (32/128 μg/mL). The results of the comparison of two agar diffusion based antimicrobial susceptibility methods, M.I.C.E and disc diffusion, revealed high relationship (R ≥0.9) for five of six antibiotics tested whereas the relationship of two methods was moderate (R=0.463) for erythromycin. Arcobacter butzleri isolates from cattle (n=5), beef (n=15), milk (n=3), water (1) and floor (n=2) were characterized by pulsed field gel electrophoresis (PFGE) using EagI restriction endonuclease and multilocus sequence typing (MLST) and high genetic diversity was observed. PFGE analysis of isolates from various sources revealed six major clusters with 16 genotypes having 50-71% similarity. Similarly high genetic diversity was seen when multilocus sequence typing was performed for two representatives of each source (cattle, beef and milk) and the results revealed that 16 of 42 (38.09%) alleles were novel alleles, which brought six new sequence types espectively. Of the resistant isolates, 3.70% and 11.11% isolates were found MDR using M.I.C.E and disc diffusion methods, respectively. The lowest minimum inhibitory concentrations (MICs), MIC50/MIC90 values were obtained for tetracycline (0.03/4 μg/mL) however highest for ampicillin (32/128 μg/mL). The results of the comparison of two agar diffusion based antimicrobial susceptibility methods, M.I.C.E and disc diffusion, revealed high relationship (R ≥0.9) for five of six antibiotics tested whereas the relationship of two methods was moderate (R=0.463) for erythromycin. Arcobacter butzleri isolates from cattle (n=5), beef (n=15), milk (n=3), water (1) and floor (n=2) were characterized by pulsed field gel electrophoresis (PFGE) using EagI restriction endonuclease and multilocus sequence typing (MLST) and high genetic diversity was observed. PFGE analysis of isolates from various sources revealed six major clusters with 16 genotypes having 50-71% similarity. Similarly high genetic diversity was seen when multilocus sequence typing was performed for two representatives of each source (cattle, beef and milk) and the results revealed that 16 of 42 (38.09%) alleles were novel alleles, which brought six new sequence types (STs). The overall dn/ds ratio was less than one (<1). When these new STs were compared with available electronic database, it showed that ST-366 (beef) was closely related (71.42%) with ST-116 which was isolated from pork in Thailand. It is concluded that the occurrence of Arcobacter spp. in animals and animal origin food products such as beef and milk, and treated water is of public health significance. Good management and hygienic practices are key factors to control the occurrence of Arcobacter at farm and market levels, respectively. In addition, antimicrobial resistance in Arcobacter spp. against commonly used antibiotics in human and veterinary therapy may increase risk of treatment failure. Tetracycline may be used as a drug of choice against Arcobacter infection. High genetic diversity in A. butzleri genome suggested that the animals and their by products were colonized by multiple Arcobacter parent genotype.